Public Works in the Canadian City; the Provision of Sewers in Toronto 1870–1913 - Brace, Catherine (Urban History Review / Revue d'histoire urbaine, 1995)
Until the 1970s Canadian public works had been adequately described, but never extensively studied in the literature of urban history, which has focused on other aspects of the city-building process. Since then, Canadian public works history has been dominated by debates about the public versus private ownership of utilities. Scant attention has been paid to sewerage, which has only been alluded to in discussions about public health and sanitation. This paper aims to show that the historical provision of sewerage in Canadian cities was a fundamental part of the city-building process. It focuses on the provision of sewers in Toronto between 1870 and 1913 and argues that sewerage influenced and was influenced by contemporary debates about public health, local government intervention in the lives of citizens and the role of technology in the urban environment.